#ChildMaltreatment and Technology - Cash, Scottye J. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2019)
Technology may seem like a friend one day, a foe another depending on how and why it is being used. In today’s world, we are inundated with social media, smart phones, tvs, and cars. Our ability to harness technology to make our lives a better place is a noble goal, however our ability to harness technology to enhance our research skills is absolutely necessary. The current paper explores the ways in which technology has been used and can be used to better understand child maltreatment and domestic violence. Overall, the message is clear, integrating technology-based research methods and practical approaches to helping vulnerable populations is one of this generations’ paradigm shifts. Technology coupled with sound research methodologies can help move us forward in our exploration and understanding of social problems and interventions.